2010
DOI: 10.5194/bg-7-3019-2010
|View full text |Cite
|
Sign up to set email alerts
|

Density/area power-law models for separating multi-scale anomalies of ore and toxic elements in stream sediments in Gejiu mineral district, Yunnan Province, China

Abstract: Abstract. This contribution introduces a fractal filtering technique newly developed on the basis of a spectral energy density vs. area power-law model in the context of multifractal theory. It can be used to map anisotropic singularities of geochemical landscapes created from geochemical concentration values in various surface media such as soils, stream sediments, tills and water. A geochemical landscape can be converted into a Fourier domain in which the spectral energy density is plotted against the area (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…According to the anisotropic scale characteristics in the frequency domain, the S-A multifractal model decomposes the spatial model into several components. After lots of practice, it has proved to be useful for breaking down complex geochemical patterns: e.g., [7,40,[79][80][81].…”
Section: Spectrum-area Multifractal Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the anisotropic scale characteristics in the frequency domain, the S-A multifractal model decomposes the spatial model into several components. After lots of practice, it has proved to be useful for breaking down complex geochemical patterns: e.g., [7,40,[79][80][81].…”
Section: Spectrum-area Multifractal Modelmentioning
confidence: 99%
“…The second group of models considers not only frequency but also spatial distributions of data. Since Mandelbrot [34] first proposed the concept of fractals, fractal technology has been widely used in geosciences and has become a powerful tool for separating different geochemical populations: e.g., [23,[35][36][37][38][39][40][41][42][43][44][45][46][47]. Geochemical exploration data generally don't conform to a normal distribution, but rather a lognormal distribution [48], and the enrichment and distribution of trace elements are characterized by multifractals [49].…”
mentioning
confidence: 99%
“…The mineralized areas are outlined by boxes: (1) Kader, (2) Godekolvari, (3) Iju, (4) Serenu, (5) Chahfiroozeh, (6) Parkam and Meiduk, and (7) Abdar and other elements to identify local anomalies. Cheng et al [17] highlighted the anomalies of trace elements using a fractal method in three different scales. Shahriari et al [18] determined the threshold angles of Spectral Angle Mapper analysis with a fractal technique to map hydrothermal alterations.…”
Section: Introductionmentioning
confidence: 99%
“…Cheng and his colleagues proposed the singularity theory (Cheng et al 2010;Cheng 2012b) based on the C-A fractal model to quantify geo-anomalies according to the invariant properties between fractal measure and scale. A number of case studies have demonstrated that the singularity index is a powerful tool to identify geochemical anomalies, to process remote sensing information, and to analyze the spatial distribution of mineral deposits Cheng 2007;Wang, Zhao, and Cheng 2011;Zuo 2011).…”
Section: Introductionmentioning
confidence: 99%